PENGARUH MEDIA TANAM DAN KONSENTRASI PUPUK ORGANIK CAIR TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN SELADA MERAH (Lactuca sativa L.) - Karim Lamawulo; Herman Rehatta; Jane I Nendissa (JURNAL BUDIDAYA PERTANIAN, 2017)
Planting media and concentration of liquid organic fertilizer were the main components that play a role as a medium to grow plants and nutrients supply for the red lettuce. To obtain appropriate planting medium and concentration of liquid organic fertilizer for growth and production of red lettuce plant, an experiment was conducted using Randomized Block Design Factorial, i.e Liquid Organic Fertilizer concentration with 6 treatment level, K0 (Without Treatment), K1 (POC 5 cc/L) (POC 20 cc/L), K4 (POC 20 cc/L) and K5 (POC 25 cc/L) and Planting Media with 3 levels i.e, M1 (3:1), M2 (4:1) and M3 (5:1). The concentration of liquid organic fertilizer gave very significant effects to the height parameters of plant (cm), number of leaves (leaf), leaf area (cm2), fresh weight of crown (g) and fresh root weight (g). Planting media had very significant effects on fresh root weight (g), ratio of root and canopy (%) and harvest index (%).